Perubahan Fisik, Fisiologi dan Biokimia Selama Pemasakan Benih dan Studi Rekalsitransi Benih Kemiri Sunan - Tresniawati, Cici; Murniati, Endang; Widajati, Eny (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTThe aims of this research on Reutealis trisperma seed were to know 1) seed harvest maturity level based on physiological and biochemical changes; and 2) seed recalcitrancy based on critical moisture content and storability in two storage temperatures. The research was conducted at Leuwikopo Seed Science and Technology Laboratory, from February 2012 to January 2013. There were three experiments, i.e. I. Effect of seed maturity level on seed viability and vigor (randomized completely block design, 3 seed maturity level, 3 replications); II. Determination of seed critical moisture content, used two methods, i.e. 1) fan drying and 2) air drying (completely randomized design in each drying methods, 3 replications); III. Effect of temperature and period of storage on seed viability and vigor (nested design, first factor was 2 storage temperature and the second factor was 7 storage periods, 3 replications). The result showed that seed physiological maturity achieved in 28 weeks after flowering with morphological criteria were brownish fruit, soft fruit exocarp, brown seed testa; physiological criteria was germination percentage 76-80% and biochemical criteria was carotenoid content 0.62 µmol(g FW)-1. Carotenoid content can be used as biochemical indicator to determine fruit maturity and significantly correlated with moisture content, seed dry weight and germination percentage. Critical moisture content were 8.2-10.9%. These data suggested that seeds could be classified as intermediate. R. trisperma seeds could be stored for three weeks in temperature 19-28 oC and RH 50-70%, with 12% moisture content used polypropilen plastic bag Keywords: carotenoid, critical moisture content, desiccation, Reutealis trisperma